2015
DOI: 10.1111/jvh.12382
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with telaprevir‐based regimens for chronic hepatitis C results in significant improvements to serum markers of liver fibrosis

Abstract: Patients infected with hepatitis C virus (HCV) have differing levels of liver health when they initiate treatment. We sought to quantify whether liver health improves following successful treatment with telaprevir-based antiviral regimens. We performed a retrospective analysis of data generated from one Phase 2 and two Phase 3 telaprevir clinical studies. 1208 patients treated with a telaprevir-based regimen were included in the analysis. Patients were grouped according to their baseline Metavir score (F0-F1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In addition, a reduction in elastometry values does not necessarily signify fibrosis regression, although the effect of SVR on liver stiffness persisted in adjusted analyses and also in sensitivity analyses, one of which used a more stringent definition of liver stiffness regression (two consecutive values showing at least a 30% improvement). Furthermore, in robustness analyses using FIB4 as a different noninvasive marker or liver fibrosis, we identified again an independent effect of SVR on regression in FIB4 values, which is in accordance with recent findings in HCV-monoinfected patients successfully treated with telaprevir-based regimens [32].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a reduction in elastometry values does not necessarily signify fibrosis regression, although the effect of SVR on liver stiffness persisted in adjusted analyses and also in sensitivity analyses, one of which used a more stringent definition of liver stiffness regression (two consecutive values showing at least a 30% improvement). Furthermore, in robustness analyses using FIB4 as a different noninvasive marker or liver fibrosis, we identified again an independent effect of SVR on regression in FIB4 values, which is in accordance with recent findings in HCV-monoinfected patients successfully treated with telaprevir-based regimens [32].…”
Section: Discussionsupporting
confidence: 89%
“…Although the use of those first-generation HCV protease inhibitors is currently limited by their toxicities, first data of fibrosis improvement were presented. Haseltine et al [56] polled data from Phase II and Phase III clinical trials with telaprevir assessing the effect of SVR on serum fibrosis markers (FibroTest, APRI, FIB-4 and Forns' Score). Among 1208 patients who reached SVR, all exhibited significant improvements in each of these noninvasive markers after treatment.…”
Section: Antiviral Drugs Affecting Liver Fibrosismentioning
confidence: 99%
“…However, many recent studies indeed have shown that improvement in serum markers correlates with decreasing fibrosis stage. 10,12,16 …”
Section: Discussionmentioning
confidence: 99%
“…Aminotransferase levels and platelet counts measured during antiviral therapy were excluded because therapy can influence these parameters. 16 The FIB4 score and APRI were summarized using a median smoother for every 90-day interval. Because of non-normality, data were log-transformed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation